VISUAL DA’WAH APPROACH: STUDY OF DESIGN PRINCIPLES THROUGH VISUAL TREND IN SOCIAL MEDIA (FACEBOOK) - Hasleena Hamzah; Faizal Kasmani; Wan Irma Sabrina Idris (Journal of Islamic, Social, Economics and Development, 2019)
Previous study on visual in da’wah consist of; comics, magazines, novels, TV series(Cinetron) and shadow puppet (Wayang Kulit). The approach denoted as engaging andalternate medium in delivering da’wah. Today, social media i.e Facebook has becoming anopen arena and a target platform in the effort to vary the medium. The used of visual are seenas relatively inventive and an influential way that are continuously substantial.This article is looking into more than 300 visual da’wah posted in designated Facebook pagesin a duration of three months. Visual da’wah are analyze through gestalt visual perception ;and identified through systematic coding and validated as a measuring factor of aesthetics invisuals. The analysis on aesthetics features of visual perception law ; The Law of Similarity,TheLaw of Direction (or ‘the law of continuity or ‘good continuation’, The Law of Closure, Figureand Ground,The Law of Inclusiveness, The Law of Symmetry and The Law of Prägnanzstufensuggesting a significant and influence of the law that is vital to establish in delivery specificda’wah content that match with the application of the law.This study suggested that Gestalt application fundamentally aid to highlight on da’wah text thatcan ensure clarity aspect in aesthetics visual da’wah approach However, the application ofgestalt law are presume not to be study independently. Other substantial finding about thisstudy are da’wah experiences that outlines constructive response that relate to muslim’s beliefthat may contribute to future da’wah approach through other social media application.